The revelatory landscape: Archiving memory through indigenous narrative and cosmology - Maponya, Mapula Jessica (School of Architecture, Planning and Geomatics, 2024)
The Khoi-Khoi's indigenous astronomical beliefs are associated with themes of time, religion and belonging. These values were manifested structurally and spiritually on the topographic landscape of Cape Town nearly 1000 years ago. Today - this landscape is merely longed for as it exclusively celebrates Colonial historical accounts. Through societal perception, nomenclature and function - this one-sided narrative is repeatedly retold while the indigenous narrative is buried and unfamiliar to many. To reveal this neglected story - this dissertation studies the physiological and historical landscape where these two societies and their varying methods of interacting with landscape through astronomy, and ideals as societies collided and subsequently birthed divide and conquer in South Africa. By unearthing and possibly memorialising overlooked indigenous heritage through excavation and archaeological design intervention - this project studies the role of Cape Town's topographic landscape in defining cultural identity. It juxtaposes these two cultures' relationships with this landscape and highlights the value and necessity of reclaiming cultural landscapes in urban contexts where indigenous narratives have been completely ignored/eradicated and reduced to myth. The site used as the tool to exhume and eventually archive this indigenous history is located on a golf course south-west of the confluence of the Black and Liesbeek river in Observatory, Cape Town. This confluence was a significant route used by the Khoi-Khoi tribe pre-colonization as a migratory route and periodic settlement zone. Both the dissertation subject and site selection were heavily informed by navigational routes used by the Dutch, British and Indigenous Societies to interact with land and additionally the vulnerability of the site in question. It is currently under development threat which one could deem as unsuitable considering that the site is an ecologically sensitive piece of land that is home to unique fauna and flora - including an endangered bird community. Of equal importance is the sites divisive political history which has permanently impacted economic and social equality post the Khoi and Dutch War(s) as well as the segregational systems that followed that moment. Could addressing the same site that established socio-political divide in South Africa be utilized to negotiate identity, memory and cultural productivity?